Penerapan Disiplin Pegawai Negeri Sipil Di Pengadilan Negeri Ambon - Ely, Hesty Kusumaningsy; Nirahua, Salmon Eliazer Marthen; Pattipawae, Dezonda Rosiana (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2023)
Introduction: The position of civil servants has a strategic role in governance. Civil servants as an instrument of government are very central because they carry and carry out components of government regulations and policies to realize the goals of the state. In order to effectively prevent the occurrence of irregularities in the implementation of duties or violations of the behavior of court officials, it is necessary to carry out continuous supervision and guidance by each direct superior to his subordinates. Purposes of the Research: to review and analyze the implementation of Government Regulation Number 94 of 2021 concerning Discipline for Civil Servants at the Ambon District Court. Methods of the Research: normative juridical research, namely a research in the field of law that aims to examine legal principles, legal principles and legal systematics. The legal materials used are primary legal materials and secondary legal materials. The problem approach used in this study is the statutory approach, and the conceptual approach. Results of the Research: Discipline violations are any words, writings, or actions of civil servants that do not comply with their obligations and/or violate the prohibition of civil servant disciplinary provisions. In November 2021 one ASN PN Ambon disobeyed obligations and violated the prohibition on civil servant disciplinary provisions both carried out inside and outside working hours by using Office Cooperative money and other deductions that were taken intentionally to be used to play online gambling and used to fulfill needs the day-to-day family according to the reasons conveyed by the civil servant, the husband of the civil servant stated that the money taken by his wife was not to meet the daily needs of the house.